A kind of water-based thermal transfer special release printing material and preparation method thereof
By applying the release layer on the polyester film and performing high-temperature extrusion transfer, the problems of residual and insufficient surface tension in the printing process of existing release materials are solved, and high-performance water-based thermal transfer special release is achieved Printing materials.
Patent Information
- Application Number
- CN202310584831.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-23
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2043-05-23
AI Technical Summary
The existing release materials are prone to residual in the printing process, resulting in poor silicon contamination and transfer effect, and low surface tension, which cannot meet the requirements of surface printing.
Polyester film (PET) is used as the printing carrier, first coat the release layer, then print the pattern and apply transfer glue, and transfer the pattern is transferred to the substrate by high-temperature extrusion. The release layer has good weather resistance and mechanical properties. .
The release layer has achieved weather resistance, chemical solvent resistance, scratch resistance and antibacterial corrosion resistance, and improved the overall performance and application prospects of printing materials.
Smart Images

Figure CN116714385B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of printing materials, and in particular to a water-based thermal transfer special release printing material and a preparation method thereof. Background Art
[0002] Special printing is a huge group of printing technologies that has been formed by combining the latest marginal science in the long-term development process. At present, there are more than 60 known processes, which are closely related to ordinary conventional printing processes (lithography, relief printing, gravure and stencil printing) and have many unique functions. It is almost suitable for any tangible material regardless of its nature, whether it is paper, fabric, leather, metal, glass, ceramics, wood, hard surface like steel or soft like egg yolk, flat or wavy appearance; from large outdoor giant advertisements to small oral capsules, through special printing plates (even abandoning printing plates), or special inks, or special printing processes, satisfactory printing effects can be obtained, creating extremely favorable conditions for the printing of various packaging materials, construction equipment, electronic components, commercial advertisements, daily life and learning supplies, artistic creation, securities, etc., as well as the value-added of commodities. Its wide range of uses includes all areas of society and all aspects of people's daily life, including clothing, food, housing, transportation, and entertainment. Therefore, special printing plays a huge role in prospering the market, meeting people's growing cultural and life needs, and beautifying the environment.
[0003] Thermal transfer, also known as heat transfer, is a method of transferring text or patterns printed on thermal transfer paper or plastic film to fabric or leather by heating and pressurizing. Its advantage is that the transferred image is brightly colored and rich in layers.
[0004] The release material for transfer is a material that acts as a peeling layer from the base film after transfer. Traditional release materials are generally silicon-containing release materials, such as silicone oil, OP wax, etc. Although the silicon-containing release material can be formulated into release layers with different peeling forces and has a good effect, it is easy to leave residues at the printing interface in subsequent printing processes, and the residual silicon-containing material is easy to cause silicon pollution. When the operator uses the silicon-containing release material, the silicon-containing residue is easily transferred to the application surface and causes subsequent transfer effects. In addition, the existing release material is only used as a peeling layer in the transfer film, and the surface tension of the silicon-containing release material is low, which cannot meet the requirements of surface printing, so it does not have a separate printing transfer function. Summary of the invention
[0005] The purpose of the present invention is to provide a water-based thermal transfer special release printing material and a preparation method thereof. A polyester film (PET) is used as a printing carrier, a release layer is first coated on the PET film, and then various patterns are printed on the release layer, and then a transfer glue is coated on the pattern. The printed pattern is transferred to a substrate through instant high-temperature extrusion. The release layer has good weather resistance, chemical solvent resistance, scratch resistance, ultraviolet radiation resistance, antibacterial and anticorrosive properties, organic matter (formaldehyde) degradation performance and mechanical properties, and has broad application prospects.
[0006] The technical solution of the present invention is achieved in this way:
[0007] The invention provides a method for preparing a water-based thermal transfer special release printing material. The method comprises the following steps: uniformly mixing a water-based thermal transfer special release coating and an ultraviolet light initiator, coating the mixture on a PE film, and curing the mixture to obtain a PE film with a release layer. A pattern is printed on the release layer using water-based ink, and a transfer adhesive is applied thereon. The mixture is then transferred to a substrate at high temperature.
[0008] As a further improvement of the present invention, the preparation method of the water-based thermal transfer special release coating is as follows:
[0009] S1. dissolving an alkyl orthosilicate in an organic solvent, adding an aqueous solution containing a surfactant and a porogen, emulsifying, adjusting the pH value of the solution, stirring the reaction, and centrifuging to obtain porous SiO2 hollow nanospheres;
[0010] S2. dissolving a soluble cerium salt, a soluble titanium salt and a complexing agent in water, adding the porous SiO2 hollow nanospheres obtained in step S1 and dispersing them evenly, adjusting the pH value of the solution, heating and evaporating to form a sol, raising the temperature to obtain a dry gel, calcining, crushing, and ball milling to obtain SiO2 nanoparticles coated with CeO2 / TiO2;
[0011] S3. dissolving the silane coupling agent in water, adjusting the pH value of the solution, and hydrolyzing to obtain an aqueous solution of the silane coupling agent after acidic hydrolysis;
[0012] S4. The CeO2 / TiO2 coated SiO2 nanoparticles obtained in step S2 are added to an ethanol aqueous solution, a surfactant is added, and the mixture is evenly dispersed, and then the aqueous solution of the acidic hydrolyzed silane coupling agent obtained in step S3 is added, and the reaction is heated and stirred to obtain a modified CeO2 / TiO2 SiO2 nanoparticle dispersion;
[0013] S5. Dissolve water-based polyurethane, fluorotitanic acid, hydrogen peroxide, and silane coupling agent in water, adjust the pH value, add the modified CeO2 / TiO2 SiO2 nanoparticle dispersion prepared in step S4, heat and stir to react, then add film-forming aid, leveling agent, defoaming agent, stir evenly, let stand and filter, and obtain a water-based thermal transfer special release coating.
[0014] As a further improvement of the present invention, the alkyl orthosilicate in step S1 is methyl orthosilicate or ethyl orthosilicate, the porogen includes a macroporous porogen and a mesoporous porogen, the macroporous porogen is selected from at least one of polyoxyethylene sorbitan fatty acid ester and polyethylene glycol octylphenyl ether; the mesoporous porogen is selected from at least one of hexadecyltrimethylammonium bromide, oxyethylene-oxypropylene triblock copolymer PEO20-PPO70-PEO20, and PEO106-PPO70-PEO106. Preferably, the porogen is a mixture of polyethylene glycol octylphenyl ether and hexadecyltrimethylammonium bromide in a mass ratio of 5-7:2; the mass ratio of the alkyl orthosilicate, the surfactant and the porogen is 20-40:1-2:2-3, the pH value of the adjusted solution is 9-10, the stirring reaction time is 5-7h, and the temperature is 40-50°C.
[0015] As a further improvement of the present invention, the soluble cerium salt in step S2 is selected from at least one of cerium nitrate, cerium sulfate, and cerium chloride; the soluble titanium salt is selected from at least one of titanium nitrate and titanium sulfate; the complexing agent is selected from at least one of citric acid, sodium citrate, malic acid, ethylenediamine, disodium EDTA, and EDTA; the mass ratio of the soluble cerium salt, the soluble titanium salt, the complexing agent, and the porous SiO2 hollow nanospheres is 3-5:4-6:15-22:15-20, the pH value of the adjusted solution is 5.5-6.5, the heating temperature is 70-80°C, the increased temperature is the temperature of the heater increased to 170-190°C, the roasting temperature is 450-550°C, the time is 2-3h, and the ball milling time is 1-2h.
[0016] As a further improvement of the present invention, the silane coupling agent in step S3 includes a mixture of KH550 and KH560 in a mass ratio of 5-7:2-3, the pH value of the adjusted solution is 5-6, and the hydrolysis time is 2-3h; the mass ratio of the SiO2 nanoparticles coated with CeO2 / TiO2 and the surfactant in step S4 is 100:3-5, the temperature of the heating and stirring reaction is 50-60°C, and the time is 1-2h.
[0017] As a further improvement of the present invention, the mass ratio of the waterborne polyurethane, fluorotitanic acid, hydrogen peroxide, silane coupling agent, film-forming aid, leveling agent and defoaming agent in step S5 is 70-90:3-5:0.5-1:2-3:2-3:1-2:2-3, the film-forming aid includes a mixture of propanol and ethylene glycol monobutyl ether in a mass ratio of 4-6:1-2; the leveling agent is selected from at least BYK-333, BYK-361N, BYK-381 A method according to the present invention; the defoaming agent is selected from at least one of BYK-053, BYK-093 and BYK-1786; the silane coupling agent is selected from at least one of KH550, KH560, KH570, KH580, KH590, KH602 and KH792; the temperature of the heating and stirring reaction is 50-70°C and the time is 2-3h; the concentration of the hydrogen peroxide is 20-22wt%; and the adjusted pH value is 8-8.5.
[0018] As a further improvement of the present invention, the silane coupling agent is a mixture of KH550 and KH792, with a mass ratio of 2-3:5-7.
[0019] As a further improvement of the present invention, the preparation method of the water-based thermal transfer special release coating is as follows:
[0020] S1. 20-40 parts by weight of methyl orthosilicate or ethyl orthosilicate are dissolved in 100 parts by weight of an organic solvent, 50 parts by weight of an aqueous solution containing 1-2 parts by weight of a surfactant and 2-3 parts by weight of a porogen are added, emulsified at 5000-7000 r / min for 3-5 min, the pH value of the solution is adjusted to 9-10, the reaction is stirred at 40-50 ° C for 5-7 h, and centrifuged to obtain porous SiO2 hollow nanospheres;
[0021] Preferably, the organic solvent is selected from at least one of ethyl acetate, methyl acetate, butyl acetate, dichloromethane, chloroform, carbon tetrachloride, petroleum ether, n-hexane and cyclohexane.
[0022] Preferably, the surfactant is selected from at least one of sodium dodecylbenzene sulfonate, sodium dodecyl sulfonate, sodium dodecyl sulfate, sodium tetradecyl sulfonate, sodium tetradecylbenzene sulfonate, sodium tetradecyl sulfate, sodium hexadecylbenzene sulfonate, sodium hexadecyl sulfonate, sodium hexadecyl sulfate, sodium octadecylbenzene sulfonate, sodium octadecyl sulfonate, and sodium octadecyl sulfate.
[0023] The porogen is a mixture of polyethylene glycol octylphenyl ether and hexadecyltrimethylammonium bromide, with a mass ratio of 5-7:2;
[0024] S2. 3-5 parts by weight of a soluble cerium salt, 4-6 parts by weight of a soluble titanium salt and 15-22 parts by weight of a complexing agent are dissolved in 50 parts by weight of water, 15-20 parts by weight of the porous SiO2 hollow nanospheres prepared in step S1 are added, ultrasonically dispersed uniformly, the solution pH is adjusted to 5.5-6.5, heated to 70-80 ° C, evaporated to form a sol, the temperature is increased to a heater temperature of 170-190 ° C, evaporated to obtain a dry gel, calcined at 450-550 ° C for 2-3h, crushed, and ball-milled for 1-2h to obtain CeO2 / TiO2-coated SiO2 nanoparticles;
[0025] S3. 5-7 parts by weight of KH550 and 2-3 parts by weight of KH560 were added to 50 parts by weight of water, the pH value of the solution was adjusted to 5-6, and hydrolyzed for 2-3h to obtain an aqueous solution of a silane coupling agent after acidic hydrolysis;
[0026] S4. Add 100 parts by weight of the CeO2 / TiO2 coated SiO2 nanoparticles obtained in step S2 to 200 parts by weight of a 45-55wt% ethanol aqueous solution, add 3-5 parts by weight of a surfactant, disperse evenly, then add 30 parts by weight of an aqueous solution of the silane coupling agent that has been acid-hydrolyzed in step S3, adjust the solution pH to 7-7.5, heat to 50-60°C, stir the reaction for 1-2h, and obtain a dispersion of modified CeO2 / TiO2 SiO2 nanoparticles;
[0027] Preferably, the surfactant is selected from at least one of dodecyltrimethylammonium chloride, dodecyldimethylammonium bromide, tetradecyltrimethylammonium chloride, tetradecyldimethylammonium bromide, hexadecyltrimethylammonium bromide, hexadecyldimethylbenzylammonium chloride, octadecyltrimethylammonium bromide and octadecyldimethylammonium chloride.
[0028] S5. Dissolve 70-90 parts by weight of waterborne polyurethane, 3-5 parts by weight of fluorotitanic acid, 0.5-1 parts by weight of 20-22wt% hydrogen peroxide, and 2-3 parts by weight of a silane coupling agent in 200 parts by weight of water, adjust the pH value to 8-8.5, add 10-12 parts by weight of the modified CeO2 / TiO2 SiO2 nanoparticle dispersion prepared in step S4, heat to 50-70°C, stir and react for 2-3h, then add 2-3 parts by weight of a film-forming aid, 1-2 parts by weight of a leveling agent, and 2-3 parts by weight of a defoaming agent, stir and mix for 20-30min, let stand for 2-3h, and filter through a 100-mesh sieve to obtain a waterborne thermal transfer special release coating;
[0029] The film-forming aid comprises a mixture of propanol and ethylene glycol monobutyl ether in a mass ratio of 4-6:1-2;
[0030] The silane coupling agent is a mixture of KH550 and KH792, with a mass ratio of 2-3:5-7.
[0031] As a further improvement of the present invention, the water-based ink is a water-based acrylic ink; the amount of wet glue applied is 5-10g / m2, and the coating speed is 50-70m / min; the curing conditions are 10-15min of curing under 100-150W ultraviolet lamp, and the high temperature is 120-150°C; the amount of transfer glue applied is 5-7g / m2, the drying oven temperature is 85-105°C, and the line speed is 70-155m / min.
[0032] The present invention further protects a water-based thermal transfer special release printing material prepared by the preparation method according to any one of claims 1 to 9.
[0033] The present invention has the following beneficial effects: the polyurethane resin contains abundant hydrophilic groups such as amino groups and can be completely soluble in water, so it can be used to prepare a special release coating for water-based thermal transfer printing. At the same time, since the polyurethane resin is alkaline, the pH value of the solution can be adjusted to be alkaline during the preparation of the coating, which is helpful for the dispersion of the polyurethane on the one hand, and on the other hand, the prepared CeO2 and TiO2 will not react under acidic conditions and reduce the load. In addition, when the pH value is higher than 8.5, the alkalinity is too strong, the viscosity of the coating is small, the drying speed is slowed down, and the water resistance is poor. When the pH value is lower than 8, the alkalinity is too weak, the viscosity of the coating is large, it is easy to dry, and defects such as dirty plates, paste plates, and bubbles will be caused.
[0034] In order to improve the performance of water-based thermal transfer special release coatings, various additives need to be added, including defoaming agents, leveling agents, film-forming additives, etc. These additives can be used scientifically to improve the defects of water-based thermal transfer special release coatings, thereby improving the stability of water-based thermal transfer special release coatings.
[0035] Water-based thermal transfer special release coating uses water as a diluent. It is cheap, widely available, harmless to the environment and human body, and is a good green solvent.
[0036] The porous SiO2 hollow nanospheres prepared by the present invention are SiO2 hollow nanosphere skeleton structures, and have the characteristics of being porous, hollow, and having a large specific surface area, etc., which are not only convenient for subsequent sol-gel reaction to immobilize CeO2 and TiO2, but also can significantly improve the chemical solvent resistance and scratch resistance of the coating, improve mechanical properties, and improve anti-aging properties, etc. when added to the special release coating for water-based thermal transfer. At the same time, the incorporation of nano-SiO2 into the coating can solve the problems of poor suspension and weather resistance of the coating, so that the coating film can be better combined with the PET material, the self-cleaning ability of the surface can also be improved, and the release force can be reduced.
[0037] The oxides loaded in the present invention include CeO2 and TiO2. Nano CeO2 is nontoxic and has good stability. It has a unique 4F electronic layer structure and abundant electronic transition energy levels. It not only has a shielding effect on UVA and UVB in ultraviolet rays, but also can absorb and reflect ultraviolet rays, showing a very strong anti-ultraviolet ability. Nano TiO2 is a stable nontoxic and tasteless ultraviolet absorber. The ultraviolet transmittance is the lowest within the wavelength range of 280-350nm. When the absorbable energy is higher than or equal to its forbidden band width 3.0eV, an electron-hole pair is generated. This electron-hole pair can be combined with other electrons and holes to produce a redox reaction, which plays a role in ultraviolet shielding. In addition, because nano TiO2 has good photocatalytic performance, it can absorb ultraviolet rays in the air to play the effects of antibacterial, antibacterial, degradation of organic matter (such as formaldehyde). Nano CeO2 and nano TiO2 contain a large amount of atomic oxygen in the crystal structure, and the oxidation activity is very high, which can produce great destructiveness to bacteria, thereby achieving a good antibacterial effect. Therefore, the compound mixture of nano-TiO2 and nano-CeO2 greatly improves the coating's UV resistance, antibacterial and anti-corrosion properties, organic matter (formaldehyde) degradation properties, green environmental protection properties and mechanical properties.
[0038] The aqueous solution of the acidic hydrolyzed silane coupling agent and the surfactant are mixed with the SiO2 nanoparticles coated with CeO2 / TiO2, so that the surfactant is adsorbed around the SiO2 nanoparticles coated with CeO2 / TiO2, so that the SiO2 nanoparticles coated with CeO2 / TiO2 can avoid agglomeration of the SiO2 nanoparticles coated with CeO2 / TiO2 under the mutual repulsion of the long-chain alkyl chain of the surfactant, thereby improving its dispersibility. At the same time, under the modification effect of the hydrolyzed silane coupling agent, the prepared modified CeO2 / TiO2 SiO2 nanoparticle dispersion is easier to be connected and modified with the polyurethane resin, so that the polyurethane resin can be uniformly modified, and the obtained water-based thermal transfer special release coating has significantly improved weather resistance, chemical solvent resistance, scratch resistance, ultraviolet radiation resistance, antibacterial and antiseptic properties, and degradation of organic matter (formaldehyde) performance, and the mechanical properties are also significantly enhanced.
[0039] The water-based thermal transfer special release printing material prepared by the invention uses polyester film (PET) as a printing carrier, firstly coats a release layer on the PET film, then prints various patterns on the release layer, and then coats a transfer glue on the pattern, and transfers the printed pattern to a substrate through instant high-temperature extrusion. The release layer has excellent weather resistance, chemical solvent resistance, scratch resistance, ultraviolet radiation resistance, antibacterial and anticorrosive properties, organic matter (formaldehyde) degradation performance and mechanical properties, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0041] Figure 1 This is the SEM image of the CeO2 / TiO2 coated SiO2 nanoparticles prepared in Preparation Example 1. DETAILED DESCRIPTION
[0042] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] The transfer adhesive is a water-based polyurethane transfer adhesive purchased from Zibo Baowei New Material Technology Co., Ltd. The water-based polyurethane is Witcobond®781, produced by Chemtura in the United States, with a density of 1.05 g / cm3; the PE film, with a thickness of 1-2 mm, was purchased from Dongguan Dongli New Materials Co., Ltd.; the water-based acrylic ink is BD-8202, with a viscosity of 1500-3500 cps (25°C), purchased from Foshan Sanshui Haocheng Synthetic Resin Co., Ltd.
[0044] Preparation Example 1 Preparation of water-based thermal transfer special release coating
[0045] The specific method is as follows:
[0046] S1. 20 parts by weight of methyl orthosilicate were dissolved in 100 parts by weight of ethyl acetate, 50 parts by weight of an aqueous solution containing 1 part by weight of sodium dodecylbenzene sulfonate and 2 parts by weight of a porogen were added, emulsified at 5000 r / min for 3 min, the solution pH was adjusted to 9, the reaction was stirred at 40 ° C for 5 h, and centrifuged at 3000 r / min for 15 min to obtain porous SiO2 hollow nanospheres;
[0047] The porogen is a mixture of polyethylene glycol octylphenyl ether and hexadecyltrimethylammonium bromide, with a mass ratio of 5:2;
[0048] S2. 3 parts by weight of cerium sulfate, 4 parts by weight of titanium sulfate and 15 parts by weight of citric acid were dissolved in 50 parts by weight of water, 15 parts by weight of the porous SiO2 hollow nanospheres prepared in step S1 were added, ultrasonically dispersed at 1000W for 20 min, the pH value of the solution was adjusted to 5.5, heated to 70°C, evaporated to form a sol, the temperature was increased to 170°C, the dry gel was evaporated, calcined at 450°C for 2h, crushed, and ball-milled for 1h to obtain SiO2 nanoparticles coated with CeO2 / TiO2; Figure 1 is the SEM image of the prepared SiO2 nanoparticles coated with CeO2 / TiO2;
[0049] S3. 5 parts by weight of KH550 and 2 parts by weight of KH560 were added to 50 parts by weight of water, the pH value of the solution was adjusted to 5, and hydrolyzed for 2h to obtain an aqueous solution of a silane coupling agent after acidic hydrolysis;
[0050] S4. Add 100 parts by weight of the CeO2 / TiO2 coated SiO2 nanoparticles obtained in step S2 to 200 parts by weight of a 45wt% ethanol aqueous solution, add 3 parts by weight of tetradecyltrimethylammonium chloride, and ultrasonically disperse for 20 minutes at 1000W, then add 30 parts by weight of the aqueous solution of the silane coupling agent that has been acid-hydrolyzed in step S3, adjust the solution pH to 7, heat to 50°C, and stir the reaction for 1h to obtain a modified CeO2 / TiO2 SiO2 nanoparticle dispersion;
[0051] S5. Dissolve 70 parts by weight of waterborne polyurethane, 3 parts by weight of fluorotitanic acid, 0.5 parts by weight of 20wt% hydrogen peroxide, and 2 parts by weight of silane coupling agent in 200 parts by weight of water, adjust the pH value to 8, add 10 parts by weight of the modified CeO2 / TiO2 SiO2 nanoparticle dispersion prepared in step S4, heat to 50°C, stir and react for 2h, then add 2 parts by weight of film-forming aid, 1 part by weight of leveling agent BYK-333, and 2 parts by weight of defoamer BYK-053, stir and mix for 20min, let stand for 2h, filter through a 100-mesh sieve, and prepare a waterborne thermal transfer special release coating;
[0052] The film-forming aid comprises a mixture of propanol and ethylene glycol monobutyl ether in a mass ratio of 4:1;
[0053] The silane coupling agent is a mixture of KH550 and KH792, with a mass ratio of 2:5.
[0054] Preparation Example 2 Preparation of water-based thermal transfer special release coating
[0055] The specific method is as follows:
[0056] S1. 40 parts by weight of tetraethyl orthosilicate was dissolved in 100 parts by weight of ethyl acetate, 50 parts by weight of an aqueous solution containing 2 parts by weight of sodium tetradecyl sulfate and 3 parts by weight of a porogen was added, emulsified at 7000 r / min for 5 min, the solution pH was adjusted to 10, the reaction was stirred at 50 ° C for 7 h, and centrifuged at 3000 r / min for 15 min to obtain porous SiO2 hollow nanospheres;
[0057] The porogen is a mixture of polyethylene glycol octylphenyl ether and hexadecyltrimethylammonium bromide, with a mass ratio of 7:2;
[0058] S2. Dissolve 5 parts by weight of cerium chloride, 6 parts by weight of titanium sulfate and 22 parts by weight of sodium citrate in 50 parts by weight of water, add 20 parts by weight of the porous SiO2 hollow nanospheres prepared in step S1, ultrasonically disperse at 1000W for 20min, adjust the solution pH to 6.5, heat to 80°C, evaporate to form a sol, increase the temperature to 190°C at the heater, evaporate to obtain a dry gel, calcine at 550°C for 3h, crush, and ball-mill for 2h to obtain CeO2 / TiO2-coated SiO2 nanoparticles;
[0059] S3. 7 parts by weight of KH550 and 3 parts by weight of KH560 were added to 50 parts by weight of water, the pH value of the solution was adjusted to 6, and hydrolyzed for 3h to obtain an aqueous solution of a silane coupling agent after acidic hydrolysis;
[0060] S4. Add 100 parts by weight of the CeO2 / TiO2 coated SiO2 nanoparticles obtained in step S2 to 200 parts by weight of a 55wt% ethanol aqueous solution, add 5 parts by weight of octadecyltrimethylammonium bromide, and ultrasonically disperse at 1000W for 20 minutes, then add 30 parts by weight of the aqueous solution of the silane coupling agent that has been acid-hydrolyzed in step S3, adjust the solution pH to 7.5, heat to 60°C, and stir the reaction for 2 hours to obtain a modified CeO2 / TiO2 SiO2 nanoparticle dispersion;
[0061] S5. 90 parts by weight of waterborne polyurethane, 5 parts by weight of fluorotitanic acid, 1 part by weight of 22wt% hydrogen peroxide, and 3 parts by weight of silane coupling agent are dissolved in 200 parts by weight of water, the pH value is adjusted to 8.5, 12 parts by weight of the modified CeO2 / TiO2 SiO2 nanoparticle dispersion prepared in step S4 are added, heated to 70°C, stirred and reacted for 3 hours, and then 3 parts by weight of film-forming aid, 2 parts by weight of leveling agent BYK-381, and 3 parts by weight of defoamer BYK-1786 are added, stirred and mixed for 30 minutes, allowed to stand for 3 hours, and filtered through a 100-mesh sieve to obtain a waterborne thermal transfer special release coating;
[0062] The film-forming aid comprises a mixture of propanol and ethylene glycol monobutyl ether in a mass ratio of 6:2;
[0063] The silane coupling agent is a mixture of KH550 and KH792, with a mass ratio of 3:7.
[0064] Preparation Example 3 Preparation of water-based thermal transfer special release coating
[0065] The specific method is as follows:
[0066] S1. 30 parts by weight of tetraethyl orthosilicate were dissolved in 100 parts by weight of ethyl acetate, 50 parts by weight of an aqueous solution containing 1.5 parts by weight of sodium hexadecylbenzene sulfonate and 2.5 parts by weight of a porogen were added, emulsified at 6000 r / min for 4 min, the pH value of the solution was adjusted to 9.5, the reaction was stirred at 45 ° C for 6 h, and centrifuged at 3000 r / min for 15 min to obtain porous SiO2 hollow nanospheres;
[0067] The porogen is a mixture of polyethylene glycol octylphenyl ether and hexadecyltrimethylammonium bromide, with a mass ratio of 6:2;
[0068] S2. Dissolve 4 parts by weight of cerium nitrate, 5 parts by weight of titanium nitrate and 20 parts by weight of citric acid in 50 parts by weight of water, add 17 parts by weight of the porous SiO2 hollow nanospheres prepared in step S1, and disperse them ultrasonically at 1000W for 20 minutes. Adjust the pH value of the solution to 6, heat to 75°C, evaporate to form a sol, increase the temperature to 180°C, evaporate to obtain a dry gel, calcine at 500°C for 2.5h, crush, and ball-mill for 1.5h to obtain SiO2 nanoparticles coated with CeO2 / TiO2;
[0069] S3. 6 parts by weight of KH550 and 2.5 parts by weight of KH560 were added to 50 parts by weight of water, the pH value of the solution was adjusted to 5.5, and hydrolyzed for 2.5h to obtain an aqueous solution of a silane coupling agent after acidic hydrolysis;
[0070] S4. Add 100 parts by weight of the CeO2 / TiO2 coated SiO2 nanoparticles obtained in step S2 to 200 parts by weight of a 50wt% ethanol aqueous solution, add 4 parts by weight of hexadecyltrimethylammonium bromide, and ultrasonically disperse for 20 minutes at 1000W, then add 30 parts by weight of the aqueous solution of the silane coupling agent that has been acid-hydrolyzed in step S3, adjust the solution pH to 7.2, heat to 55°C, and stir the reaction for 1.5h to obtain a modified CeO2 / TiO2 SiO2 nanoparticle dispersion;
[0071] S5. 80 parts by weight of waterborne polyurethane, 4 parts by weight of fluorotitanic acid, 0.7 parts by weight of 21wt% hydrogen peroxide, and 2.5 parts by weight of silane coupling agent were dissolved in 200 parts by weight of water, the pH value was adjusted to 8.2, 11 parts by weight of the modified CeO2 / TiO2 SiO2 nanoparticle dispersion prepared in step S4 were added, heated to 60°C, stirred and reacted for 2.5 hours, and then 2.5 parts by weight of film-forming aid, 1.5 parts by weight of leveling agent BYK-361 N, and 2.5 parts by weight of defoamer BYK-093 were added, stirred and mixed for 25 minutes, allowed to stand for 2.5 hours, and filtered through a 100-mesh sieve to obtain a waterborne thermal transfer special release coating;
[0072] The film-forming aid comprises a mixture of propanol and ethylene glycol monobutyl ether in a mass ratio of 5:1.5;
[0073] The silane coupling agent is a mixture of KH550 and KH792, with a mass ratio of 2.5:6.
[0074] Preparation Example 4
[0075] Compared with Preparation Example 3, the difference is that the silane coupling agent in step S5 is a single KH550.
[0076] Preparation Example 5
[0077] Compared with Preparation Example 3, the difference is that the silane coupling agent in step S5 is a single KH792.
[0078] Preparation Example 6
[0079] Compared with Preparation Example 3, the difference is that the porogen in step S1 is a single polyethylene glycol octylphenyl ether.
[0080] Preparation Example 7
[0081] Compared with Preparation Example 3, the difference is that the porogen in step S1 is a single hexadecyltrimethylammonium bromide.
[0082] Comparative Preparation Example 1
[0083] Compared with Preparation Example 3, the difference is that no porogen is added in step S1.
[0084] The details are as follows:
[0085] S1. Dissolve 30 parts by weight of tetraethyl orthosilicate in 100 parts by weight of ethyl acetate, add 50 parts by weight of an aqueous solution containing 1.5 parts by weight of sodium hexadecylbenzenesulfonate, emulsify at 6000 r / min for 4 min, adjust the solution pH to 9.5, stir the reaction at 45°C for 6 h, and centrifuge at 3000 r / min for 15 min to obtain SiO2 hollow nanospheres.
[0086] Comparative Preparation Example 2
[0087] Compared with Preparation Example 3, the difference is that cerium nitrate is not added in step S2.
[0088] The details are as follows:
[0089] S2. Dissolve 9 parts by weight of titanium nitrate and 20 parts by weight of citric acid in 50 parts by weight of water, add 17 parts by weight of the porous SiO2 hollow nanospheres obtained in step S1, ultrasonically disperse at 1000W for 20 minutes, adjust the pH value of the solution to 6, heat to 75°C, evaporate to form a sol, increase the temperature to 180°C of the heater, evaporate to obtain a dry gel, calcine at 500°C for 2.5 hours, crush, and ball-mill for 1.5 hours to obtain SiO2 nanoparticles coated with TiO2.
[0090] Comparative Preparation Example 3
[0091] Compared with Preparation Example 3, the difference is that titanium nitrate is not added in step S2.
[0092] The details are as follows:
[0093] S2. Dissolve 9 parts by weight of cerium nitrate and 20 parts by weight of citric acid in 50 parts by weight of water, add 17 parts by weight of the porous SiO2 hollow nanospheres obtained in step S1, ultrasonically disperse at 1000W for 20 minutes, adjust the pH value of the solution to 6, heat to 75°C, evaporate to form a sol, increase the temperature to 180°C of the heater, evaporate to obtain a dry gel, calcine at 500°C for 2.5 hours, crush, and ball-mill for 1.5 hours to obtain SiO2 nanoparticles coated with CeO2.
[0094] Comparative Preparation Example 4
[0095] Compared with Preparation Example 3, the difference is that step S2 is not performed.
[0096] The details are as follows:
[0097] S1. 30 parts by weight of tetraethyl orthosilicate were dissolved in 100 parts by weight of ethyl acetate, 50 parts by weight of an aqueous solution containing 1.5 parts by weight of sodium hexadecylbenzene sulfonate and 2.5 parts by weight of a porogen were added, emulsified at 6000 r / min for 4 min, the pH value of the solution was adjusted to 9.5, the reaction was stirred at 45 ° C for 6 h, and centrifuged at 3000 r / min for 15 min to obtain porous SiO2 hollow nanospheres;
[0098] The porogen is a mixture of polyethylene glycol octylphenyl ether and hexadecyltrimethylammonium bromide, with a mass ratio of 6:2;
[0099] S2. 6 parts by weight of KH550 and 2.5 parts by weight of KH560 were added to 50 parts by weight of water, the pH value of the solution was adjusted to 5.5, and hydrolyzed for 2.5h to obtain an aqueous solution of a silane coupling agent after acidic hydrolysis;
[0100] S3. 100 parts by weight of the porous SiO2 hollow nanospheres prepared in step S1 were added to 200 parts by weight of a 50wt% ethanol aqueous solution, 4 parts by weight of hexadecyltrimethylammonium bromide were added, and ultrasonic dispersion was performed at 1000W for 20 min, and then 30 parts by weight of an aqueous solution of the silane coupling agent that had been acid-hydrolyzed in step S3 were added, the pH value of the solution was adjusted to 7.2, heated to 55°C, and stirred for 1.5h to obtain a modified porous SiO2 hollow nanosphere dispersion;
[0101] S4. 80 parts by weight of waterborne polyurethane, 4 parts by weight of fluorotitanic acid, 0.7 parts by weight of 21wt% hydrogen peroxide, and 2.5 parts by weight of silane coupling agent were dissolved in 200 parts by weight of water, the pH value was adjusted to 8.2, 11 parts by weight of the modified porous SiO2 hollow nanosphere dispersion prepared in step S3 were added, heated to 60°C, stirred and reacted for 2.5 hours, and then 2.5 parts by weight of film-forming aid, 1.5 parts by weight of leveling agent BYK-361 N, and 2.5 parts by weight of defoamer BYK-093 were added, stirred and mixed for 25 minutes, allowed to stand for 2.5 hours, and filtered through a 100-mesh sieve to obtain a waterborne thermal transfer special release coating;
[0102] The film-forming aid comprises a mixture of propanol and ethylene glycol monobutyl ether in a mass ratio of 5:1.5;
[0103] The silane coupling agent is a mixture of KH550 and KH792, with a mass ratio of 2.5:6.
[0104] Comparative Preparation Example 5
[0105] Compared with Preparation Example 3, the difference is that hexadecyltrimethylammonium bromide is not added in step S4.
[0106] The details are as follows:
[0107] S4. Add 100 parts by weight of the CeO2 / TiO2 coated SiO2 nanoparticles obtained in step S2 to 200 parts by weight of a 50wt% ethanol aqueous solution, and ultrasonically disperse at 1000W for 20 minutes. Then, add 30 parts by weight of the aqueous solution of the silane coupling agent that has been acid-hydrolyzed in step S3, adjust the pH value of the solution to 7.2, heat to 55°C, and stir the reaction for 1.5 hours to obtain a dispersion of modified CeO2 / TiO2 SiO2 nanoparticles.
[0108] Comparative Preparation Example 6
[0109] Compared with Preparation Example 3, the difference is that the aqueous solution of the silane coupling agent that has been hydrolyzed by acid is not added in step S4.
[0110] The details are as follows:
[0111] S4. Add 100 parts by weight of the CeO2 / TiO2 coated SiO2 nanoparticles obtained in step S2 to 200 parts by weight of a 50wt% ethanol aqueous solution, add 4 parts by weight of hexadecyltrimethylammonium bromide, ultrasonically disperse at 1000W for 20 minutes, adjust the solution pH to 7.2, heat to 55°C, stir and react for 1.5 hours to obtain a dispersion of modified CeO2 / TiO2 SiO2 nanoparticles.
[0112] Comparative Preparation Example 7
[0113] Compared with Preparation Example 3, the difference is that step S4 is not performed.
[0114] The details are as follows:
[0115] S1. 30 parts by weight of tetraethyl orthosilicate were dissolved in 100 parts by weight of ethyl acetate, 50 parts by weight of an aqueous solution containing 1.5 parts by weight of sodium hexadecylbenzene sulfonate and 2.5 parts by weight of a porogen were added, emulsified at 6000 r / min for 4 min, the pH value of the solution was adjusted to 9.5, the reaction was stirred at 45 ° C for 6 h, and centrifuged at 3000 r / min for 15 min to obtain porous SiO2 hollow nanospheres;
[0116] The porogen is a mixture of polyethylene glycol octylphenyl ether and hexadecyltrimethylammonium bromide, with a mass ratio of 6:2;
[0117] S2. Dissolve 4 parts by weight of cerium nitrate, 5 parts by weight of titanium nitrate and 20 parts by weight of citric acid in 50 parts by weight of water, add 17 parts by weight of the porous SiO2 hollow nanospheres prepared in step S1, and disperse them ultrasonically at 1000W for 20 minutes. Adjust the pH value of the solution to 6, heat to 75°C, evaporate to form a sol, increase the temperature to 180°C, evaporate to obtain a dry gel, calcine at 500°C for 2.5h, crush, and ball-mill for 1.5h to obtain SiO2 nanoparticles coated with CeO2 / TiO2;
[0118] S3. 80 parts by weight of waterborne polyurethane, 4 parts by weight of fluorotitanic acid, 0.7 parts by weight of 21wt% hydrogen peroxide, and 2.5 parts by weight of silane coupling agent were dissolved in 200 parts by weight of water, the pH value was adjusted to 8.2, 11 parts by weight of CeO2 / TiO2-coated SiO2 nanoparticles prepared in step S2 were added, heated to 60°C, stirred and reacted for 2.5 hours, and then 2.5 parts by weight of film-forming aid, 1.5 parts by weight of leveling agent BYK-361 N, and 2.5 parts by weight of defoamer BYK-093 were added, stirred and mixed for 25 minutes, allowed to stand for 2.5 hours, and filtered through a 100-mesh sieve to obtain a waterborne thermal transfer special release coating;
[0119] The film-forming aid comprises a mixture of propanol and ethylene glycol monobutyl ether in a mass ratio of 5:1.5;
[0120] The silane coupling agent is a mixture of KH550 and KH792, with a mass ratio of 2.5:6.
[0121] Comparative Preparation Example 8
[0122] Compared with Preparation Example 3, the difference is that no silane coupling agent is added in step S5.
[0123] The details are as follows:
[0124] S5. Dissolve 80 parts by weight of waterborne polyurethane, 4 parts by weight of fluorotitanic acid, and 0.7 parts by weight of 21wt% hydrogen peroxide in 200 parts by weight of water, adjust the pH value to 8.2, add 11 parts by weight of the modified CeO2 / TiO2 SiO2 nanoparticle dispersion prepared in step S4, heat to 60°C, stir and react for 2.5 hours, then add 2.5 parts by weight of film-forming aid, 1.5 parts by weight of leveling agent BYK-361N, and 2.5 parts by weight of defoaming agent BYK-093, stir and mix for 25 minutes, let stand for 2.5 hours, filter through a 100-mesh sieve, and obtain a waterborne thermal transfer special release coating.
[0125] Comparative Preparation Example 9
[0126] Compared with Preparation Example 3, the difference is that the modified CeO2 / TiO2 SiO2 nanoparticle dispersion is not added in step S5.
[0127] The details are as follows:
[0128] S5. Dissolve 80 parts by weight of waterborne polyurethane, 4 parts by weight of fluorotitanic acid, 0.7 parts by weight of 21wt% hydrogen peroxide, and 2.5 parts by weight of silane coupling agent in 200 parts by weight of water, adjust the pH value to 8.2, heat to 60°C, stir and react for 2.5 hours, then add 2.5 parts by weight of film-forming aid, 1.5 parts by weight of leveling agent BYK-361 N, and 2.5 parts by weight of defoaming agent BYK-093, stir and mix for 25 minutes, let stand for 2.5 hours, filter through a 100-mesh sieve, and obtain a waterborne thermal transfer special release coating.
[0129] Comparative Preparation Example 10
[0130] Compared with Preparation Example 3, the difference is that no fluorotitanic acid is added in step S5.
[0131] The details are as follows:
[0132] S5. Dissolve 80 parts by weight of waterborne polyurethane, 0.7 parts by weight of 21wt% hydrogen peroxide, and 2.5 parts by weight of silane coupling agent in 200 parts by weight of water, adjust the pH value to 8.2, add 11 parts by weight of the modified CeO2 / TiO2 SiO2 nanoparticle dispersion prepared in step S4, heat to 60°C, stir and react for 2.5 hours, then add 2.5 parts by weight of film-forming aid, 1.5 parts by weight of leveling agent BYK-361 N, and 2.5 parts by weight of defoaming agent BYK-093, stir and mix for 25 minutes, let stand for 2.5 hours, filter through a 100-mesh sieve, and obtain a waterborne thermal transfer special release coating. Example 1
[0133] The present embodiment provides a method for preparing a water-based thermal transfer special release printing material. The water-based thermal transfer special release coating prepared in Preparation Example 1 and the ultraviolet light initiator Darocur 1173 are uniformly mixed in a mass ratio of 1000:1, and coated on a PE film. The amount of wet glue coated is 5 g / m2, the coating speed is 50 m / min, and the film is irradiated and cured with a 100 W ultraviolet lamp for 10 minutes to obtain a PE film with a release layer. A pattern is printed on the release layer with water-based acrylic ink, and a transfer glue is applied. The amount of the transfer glue coated is 5 g / m2. The drying oven temperature is 85°C, the line speed is 70 m / min, and the film is transferred to a substrate at 120°C. Example 2
[0134] The present embodiment provides a method for preparing a water-based thermal transfer special release printing material. The water-based thermal transfer special release coating prepared in Preparation Example 2 and the ultraviolet light initiator Darocur 1173 are uniformly mixed in a mass ratio of 1000:1, and coated on a PE film. The amount of wet glue coated is 10 g / m2, the coating speed is 70 m / min, and the film is irradiated and cured with a 150 W ultraviolet lamp for 15 minutes to obtain a PE film with a release layer. A pattern is printed on the release layer with water-based acrylic ink, and a transfer glue is applied. The amount of the transfer glue coated is 7 g / m2. The drying oven temperature is 105° C., the line speed is 155 m / min, and the film is transferred to a substrate at 150° C. Example 3
[0135] The present embodiment provides a method for preparing a water-based thermal transfer special release printing material. The water-based thermal transfer special release coating prepared in Preparation Example 3 and the ultraviolet light initiator Darocur 1173 are uniformly mixed in a mass ratio of 1000:1, and coated on a PE film. The amount of wet glue coated is 7 g / m2, the coating speed is 60 m / min, and the film is irradiated and cured with a 120 W ultraviolet lamp for 12 minutes to obtain a PE film with a release layer. A pattern is printed on the release layer with water-based acrylic ink, and a transfer glue is applied. The amount of the transfer glue coated is 6 g / m2. The drying oven temperature is 95°C, the line speed is 115 m / min, and the film is transferred to a substrate at 135°C.
[0136] Compared with Example 3, Examples 4-7 and Comparative Examples 1-10 differ in that the water-based thermal transfer special release coatings are prepared from Preparation Examples 4-7 and Comparative Preparation Examples 1-10, respectively.
[0137] Test Example 1
[0138] The water-based thermal transfer special release printing materials prepared in Examples 1-7 of the present invention and Comparative Examples 1-10 were subjected to performance tests. The results are shown in Table 1.
[0139] Table 1
[0140] Group Release force (g / 25cm) Release residual rate after transfer (%) Ink adhesion (grade) Transfer fastness (%) Example 1 32.5 0.02 0 99.2 Example 2 32.9 0.03 0 99.0 Example 3 32.2 0.01 0 99.5 Example 4 32.9 0.07 0 97.2 Example 5 32.8 0.09 0 97.4 Example 6 32.6 0.05 0 98.5 Example 7 32.7 0.07 0 98.1 Comparative Example 1 32.9 0.09 0 98.0 Comparative Example 2 33.1 0.04 0 98.3 Comparative Example 3 32.9 0.06 0 98.2 Comparative Example 4 33.2 0.07 0 97.9 Comparative Example 5 33.9 0.10 0 97.3 Comparative Example 6 34.5 0.14 0 96.5 Comparative Example 7 34.9 0.19 1 96.0 Comparative Example 8 33.0 0.15 1 96.8 Comparative Example 9 34.4 0.11 1 97.1 Comparative Example 10 49.2 4.21 1 98.6
[0141] It can be seen from the above table that the water-based thermal transfer special release printing material prepared by the present invention has better comprehensive performance.
[0142] Test Example 2 Abrasion resistance test
[0143] After curing, the water-based thermal transfer special release coatings coated on the PE film in Examples 1-7 and Comparative Examples 1-10 were placed on a friction tester. After the test started, one round trip was counted as one time. The number of times the machine had run after the start of the experiment when friction scratches began to appear on the sample was recorded. The more times, the better the wear resistance of the coating.
[0144] The results are shown in Table 2.
[0145] Table 2
[0146] Group Coating wear resistance (times) Example 1 37 Example 2 39 Example 3 41 Example 4 33 Example 5 34 Example 6 32 Example 7 31 Comparative Example 1 29 Comparative Example 2 28 Comparative Example 3 27 Comparative Example 4 25 Comparative Example 5 30 Comparative Example 6 31 Comparative Example 7 28 Comparative Example 8 31 Comparative Example 9 22 Comparative Example 10 36
[0147] It can be seen from the above table that the samples prepared in Examples 1-3 of the present invention have good wear resistance.
[0148] Test Example 3 Antibacterial Test
[0149] After the water-based thermal transfer special release coatings coated on the PE film in Examples 1-7 and Comparative Examples 1-10 were cured, the sterilization rate was characterized by the Escherichia coli bacterial liquid drop method, that is, the bacterial liquid existed in the form of droplets on the surface of the sample, and the initial bacterial concentration per unit area was subtracted from the bacterial concentration per unit area after the experimental material was irradiated with light, and then divided by the initial bacterial concentration per unit area to obtain the sterilization rate. The light source used in the experiment was an 8W 254nm ultraviolet lamp.
[0150] Sterilization rate (%) = (initial bacterial concentration per unit area - bacterial concentration per unit area of experimental material after illumination) / initial bacteria per unit area × 100%
[0151] The results are shown in Table 3.
[0152] Table 3
[0153] Group Sterilization rate (%) Example 1 99.9 Example 2 99.9 Example 3 99.9 Example 4 99.4 Example 5 99.1 Example 6 92.2 Example 7 93.1 Comparative Example 1 90.4 Comparative Example 2 84.5 Comparative Example 3 82.9 Comparative Example 4 73.1 Comparative Example 5 87.5 Comparative Example 6 86.9 Comparative Example 7 84.9 Comparative Example 8 98.9 Comparative Example 9 69.8 Comparative Example 10 98.8
[0154] It can be seen from the above table that the samples prepared in Examples 1-3 of the present invention have good antibacterial properties.
[0155] Test Example 4
[0156] After the water-based thermal transfer special release coatings coated on the PE film in Examples 1-7 and Comparative Examples 1-10 were cured, they were tested according to the following method.
[0157] Tensile strength: tested according to DIN EN ISO 527-3 / 2 / 200, 2003-07;
[0158] Weather resistance: Tested according to IEC 61215 method, conditions are 85℃×85%RH, requirement>2000h.
[0159] UV resistance: artificial accelerated aging test under 270W, 365nm ultraviolet light irradiation conditions, and calculate the aging resistance time.
[0160] The results are shown in Table 4.
[0161]
[0162] It can be seen from the above table that the samples prepared in Examples 1-3 of the present invention have good mechanical properties, weather resistance and UV resistance.
[0163] Compared with Example 3, Examples 4-7 and Comparative Examples 1-10 differ in that the water-based thermal transfer special release coatings are prepared from Preparation Examples 4-7 and Comparative Preparation Examples 1-10, respectively.
[0164] Compared with Preparation Example 3, Preparation Examples 4 and 5 have a single KH550 or KH792 as the silane coupling agent in step S5. Compared with Preparation Example 3, no silane coupling agent is added in Step S5 in Comparative Preparation Example 8. The release residual rate after transfer is improved, the transfer fastness decreases, the adhesion decreases, the mechanical properties decrease, and the wear resistance of the coating decreases. KH550 or KH792 is a silane coupling agent with an amino group. Under the synergistic effect of the two, KH550 has one amino group and KH792 has two amino groups. Under the coordinated effect of the two, the hydrogen bonding between the polyurethane resin and the modified CeO2 / TiO2 SiO2 nanoparticle dispersion can be significantly promoted, and the amino group can also react with the polyurethane, so that the bonding is tighter and various properties are significantly improved.
[0165] Compared with Preparation Example 3, Preparation Examples 6 and 7 have a porogen in step S1 that is a single polyethylene glycol octylphenyl ether or hexadecyltrimethylammonium bromide. Comparison of Centrifugal Force Compared with Preparation Example 3, no porogen is added in step S1. Mechanical properties are reduced, the wear resistance of the coating is reduced, the sterilization rate is reduced, and the UV resistance is reduced. The porous SiO2 hollow nanospheres prepared by the present invention are SiO2 hollow nanosphere skeleton structures, which have the characteristics of being porous, hollow, and having a large specific surface area. Not only can it be convenient for subsequent sol-gel reactions to immobilize CeO2 and TiO2, but it can also be added to the special release coating for water-based thermal transfer, and can also significantly improve the chemical solvent resistance and scratch resistance of the coating, improve mechanical properties, and improve anti-aging properties.
[0166] Compared with Preparation Example 3, no cerium nitrate or titanium nitrate is added in step S2. Compared with Preparation Example 3, step S2 is not performed in Preparation Example 4. Mechanical properties decline, coating wear resistance declines, sterilization rate declines, ultraviolet resistance declines, weather resistance declines, and mechanical properties decline. The oxide loaded in the present invention includes CeO2 and TiO2, and nano CeO2 is nontoxic and has good stability, has a unique 4F electronic layer structure and abundant electronic transition energy levels, not only has a shielding effect on UVA and UVB in ultraviolet rays, but also can absorb and reflect ultraviolet rays, showing very strong anti-ultraviolet ability. Nano TiO2 is a stable nontoxic, tasteless ultraviolet absorber, and the ultraviolet transmittance is the lowest within the wavelength range of 280-350nm, and when the absorbable energy is higher than or equal to its forbidden band width 3.0eV, an electron-hole pair is generated, and this electron-hole pair can be compounded with other electrons and holes for redox reaction, and plays an ultraviolet shielding effect. In addition, since nano-TiO2 has good photocatalytic properties, it can absorb ultraviolet rays in the air to play a role in antibacterial, antibacterial, and degradation of organic matter (such as formaldehyde). The crystal structure of nano-CeO2 and nano-TiO2 contains a large amount of atomic oxygen, and the oxidation activity is very high, which can be extremely destructive to bacteria, thereby achieving a good antibacterial effect. Therefore, the compounding of nano-TiO2 and nano-CeO2 greatly improves the anti-ultraviolet performance, antibacterial and anti-corrosion performance, degradation of organic matter (formaldehyde) performance, green environmental protection performance and mechanical properties of the coating.
[0167] Compared with Preparation Example 3, in Comparative Preparation Example 5, hexadecyltrimethylammonium bromide was not added in step S4. Compared with Preparation Example 3, in Comparative Preparation Example 6, an aqueous solution of a silane coupling agent subjected to acidic hydrolysis was not added in step S4. Compared with Preparation Example 3, in Comparative Preparation Example 7, step S4 was not performed. Adhesion decreased, transfer fastness decreased, coating wear resistance decreased, mechanical properties decreased, sterilization rate decreased, UV resistance decreased, weather resistance decreased, and mechanical properties decreased. The aqueous solution of the acidic hydrolyzed silane coupling agent and the surfactant are mixed with the SiO2 nanoparticles coated with CeO2 / TiO2, so that the surfactant is adsorbed around the SiO2 nanoparticles coated with CeO2 / TiO2, so that the SiO2 nanoparticles coated with CeO2 / TiO2 can avoid agglomeration of the SiO2 nanoparticles coated with CeO2 / TiO2 under the mutual repulsion of the long-chain alkyl chain of the surfactant, thereby improving its dispersibility. At the same time, under the modification effect of the hydrolyzed silane coupling agent, the prepared modified CeO2 / TiO2 SiO2 nanoparticle dispersion is easier to be connected and modified with the polyurethane resin, so that the polyurethane resin can be uniformly modified, and the obtained water-based thermal transfer special release coating has significantly improved weather resistance, chemical solvent resistance, scratch resistance, ultraviolet radiation resistance, antibacterial and antiseptic properties, and degradation of organic matter (formaldehyde) performance, and the mechanical properties are also significantly enhanced.
[0168] Comparative Preparation Example 9 Compared with Preparation Example 3, no modified CeO2 / TiO2 SiO2 nanoparticle dispersion was added in step S5. The coating had reduced wear resistance, reduced mechanical properties, reduced sterilization rate, reduced UV resistance, and reduced weather resistance.
[0169] Compared with Preparation Example 3, Preparation Example 10 does not add fluorotitanic acid in step S5. The release force is improved, and the addition of fluorotitanic acid introduces fluorine-containing groups into the coating, thereby reducing the release force, promoting the release effect of the coating, and reducing the release residue after transfer.
[0170] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a water-based thermal transfer special release printing material, characterized in that: The water-based thermal transfer special release coating and the ultraviolet light initiator are mixed evenly, coated on a PE film, and after curing, a PE film with a release layer is obtained, a pattern is printed on the release layer with a water-based ink, a transfer glue is applied, and the film is transferred to a substrate; the preparation method of the water-based thermal transfer special release coating is as follows: porous SiO2 hollow nanospheres are prepared by a sol-gel method, and then CeO2 and TiO2 are deposited and coated on the surface, and then modified by a surfactant and an aqueous solution of an acid-hydrolyzed silane coupling agent, mixed with water-based polyurethane, fluorotitanic acid, hydrogen peroxide, and a silane coupling agent, a film-forming aid, a leveling agent, and a defoaming agent are added, stirred evenly, and filtered after standing to obtain the water-based thermal transfer special release coating.
2. The method for preparing the water-based thermal transfer special release printing material according to claim 1, characterized in that: The preparation method of the water-based thermal transfer special release coating is as follows: S1. dissolving an alkyl orthosilicate in an organic solvent, adding an aqueous solution containing a surfactant and a porogen, emulsifying, adjusting the pH value of the solution, stirring the reaction, and centrifuging to obtain porous SiO2 hollow nanospheres; S2. The soluble cerium salt, the soluble titanium salt and the complexing agent are dissolved in water, the porous SiO2 hollow nanospheres prepared in step S1 are added and dispersed evenly, the pH value of the solution is adjusted, the sol is formed by heating and evaporation, the temperature is increased to obtain a dry gel, calcined, crushed, and ball-milled to obtain SiO2 nanoparticles coated with CeO2 and TiO2; S3. dissolving the silane coupling agent in water, adjusting the pH value of the solution, and hydrolyzing to obtain an aqueous solution of the silane coupling agent after acidic hydrolysis; S4. The CeO2 and TiO2 coated SiO2 nanoparticles obtained in step S2 are added to an ethanol aqueous solution, a surfactant is added, and the mixture is evenly dispersed, and then the aqueous solution of the silane coupling agent obtained in step S3 after acidic hydrolysis is added, and the reaction is heated and stirred to obtain a dispersion of modified CeO2 and TiO2 SiO2 nanoparticles; S5. Dissolve water-based polyurethane, fluorotitanic acid, hydrogen peroxide and silane coupling agent in water, adjust the pH value, add the modified CeO2 and TiO2 SiO2 nanoparticle dispersion prepared in step S4, heat and stir to react, then add film-forming aid, leveling agent and defoaming agent, stir evenly, let stand and filter to obtain a water-based thermal transfer special release coating.
3. The method for preparing the water-based thermal transfer special release printing material according to claim 2, characterized in that: The alkyl orthosilicate in step S1 is methyl orthosilicate or ethyl orthosilicate, the porogen includes a macroporous porogen and a mesoporous porogen, the macroporous porogen is selected from at least one of polyoxyethylene sorbitan fatty acid ester and polyethylene glycol octylphenyl ether; the mesoporous porogen is selected from at least one of hexadecyltrimethylammonium bromide, ethylene oxide-propylene oxide triblock copolymer PEO20-PPO70-PEO20, and PEO106-PPO70-PEO106, the mass ratio of the alkyl orthosilicate, the surfactant and the porogen is 20-40:1-2:2-3, the pH value of the solution is adjusted to 9-10, the stirring reaction time is 5-7h, and the temperature is 40-50°C.
4. The method for preparing the water-based thermal transfer special release printing material according to claim 3, characterized in that: The porogen is a mixture of polyethylene glycol octylphenyl ether and hexadecyltrimethylammonium bromide, with a mass ratio of 5-7:
2.
5. The method for preparing the water-based thermal transfer special release printing material according to claim 2, characterized in that: The soluble cerium salt in step S2 is selected from at least one of cerium nitrate, cerium sulfate, and cerium chloride; the soluble titanium salt is selected from at least one of titanium nitrate and titanium sulfate; the complexing agent is selected from at least one of citric acid, sodium citrate, malic acid, ethylenediamine, disodium EDTA, and EDTA; the mass ratio of the soluble cerium salt, the soluble titanium salt, the complexing agent, and the porous SiO2 hollow nanospheres is 3-5:4-6:15-22:15-20, the pH value of the adjusted solution is 5.5-6.5, the heating temperature is 70-80°C, the increased temperature is the temperature of the heater increased to 170-190°C, the roasting temperature is 450-550°C, the time is 2-3h, and the ball milling time is 1-2h.
6. The method for preparing the water-based thermal transfer special release printing material according to claim 2, characterized in that: The silane coupling agent in step S3 includes a mixture of KH550 and KH560 in a mass ratio of 5-7:2-3, the pH value of the adjusted solution is 5-6, and the hydrolysis time is 2-3h; the mass ratio of the SiO2 nanoparticles coated with CeO2 and TiO2 and the surfactant in step S4 is 100:3-5, the temperature of the heated and stirred reaction is 50-60°C, and the time is 1-2h.
7. The method for preparing the water-based thermal transfer special release printing material according to claim 2, characterized in that: The mass ratio of the waterborne polyurethane, fluorotitanic acid, hydrogen peroxide, silane coupling agent, film-forming aid, leveling agent and defoaming agent in step S5 is 70-90:3-5:0.5-1:2-3:2-3:1-2:2-3, the film-forming aid comprises a mixture of propanol and ethylene glycol monobutyl ether in a mass ratio of 4-6:1-2; the leveling agent is selected from at least one of BYK-333, BYK-361N and BYK-381; the defoaming agent At least one selected from BYK-053, BYK-093, BYK-1786; the silane coupling agent in step S5 is selected from at least one selected from KH550, KH560, KH570, KH580, KH590, KH602, KH792; the temperature of the heating and stirring reaction is 50-70°C, and the time is 2-3h; the concentration of the hydrogen peroxide is 20-22wt%; and the adjusted pH value is 8-8.
5.
8. The method for preparing the water-based thermal transfer special release printing material according to claim 7, characterized in that: The silane coupling agent in step S5 is a mixture of KH550 and KH792, with a mass ratio of 2-3:5-7.
9. The method for preparing the water-based thermal transfer special release printing material according to claim 2, characterized in that: The preparation method of the water-based thermal transfer special release coating is as follows: S1. 20-40 parts by weight of methyl orthosilicate or ethyl orthosilicate are dissolved in 100 parts by weight of an organic solvent, 50 parts by weight of an aqueous solution containing 1-2 parts by weight of a surfactant and 2-3 parts by weight of a porogen are added, emulsified at 5000-7000 r / min for 3-5 min, the pH value of the solution is adjusted to 9-10, the reaction is stirred at 40-50 ° C for 5-7 h, and centrifuged to obtain porous SiO2 hollow nanospheres; The porogen is a mixture of polyethylene glycol octylphenyl ether and hexadecyltrimethylammonium bromide, with a mass ratio of 5-7:2; S2. 3-5 parts by weight of a soluble cerium salt, 4-6 parts by weight of a soluble titanium salt and 15-22 parts by weight of a complexing agent are dissolved in 50 parts by weight of water, 15-20 parts by weight of the porous SiO2 hollow nanospheres prepared in step S1 are added, ultrasonically dispersed uniformly, the solution pH is adjusted to 5.5-6.5, heated to 70-80 ° C, evaporated to form a sol, the temperature is increased to a temperature of the heater of 170-190 ° C, evaporated to obtain a dry gel, calcined at 450-550 ° C for 2-3h, crushed, and ball-milled for 1-2h to obtain SiO2 nanoparticles coated with CeO2 and TiO2; S3. 5-7 parts by weight of KH550 and 2-3 parts by weight of KH560 were added to 50 parts by weight of water, the pH value of the solution was adjusted to 5-6, and hydrolyzed for 2-3h to obtain an aqueous solution of a silane coupling agent after acidic hydrolysis; S4. Add 100 parts by weight of the CeO2 and TiO2 coated SiO2 nanoparticles obtained in step S2 to 200 parts by weight of a 45-55wt% ethanol aqueous solution, add 3-5 parts by weight of a surfactant, disperse evenly, then add 30 parts by weight of an aqueous solution of a silane coupling agent that has been acid-hydrolyzed in step S3, adjust the solution pH to 7-7.5, heat to 50-60°C, stir the reaction for 1-2h, and obtain a dispersion of modified CeO2 and TiO2 SiO2 nanoparticles; S5. Dissolve 70-90 parts by weight of waterborne polyurethane, 3-5 parts by weight of fluorotitanic acid, 0.5-1 parts by weight of 20-22wt% hydrogen peroxide, and 2-3 parts by weight of a silane coupling agent in 200 parts by weight of water, adjust the pH value to 8-8.5, add 10-12 parts by weight of a dispersion of SiO2 nanoparticles of modified CeO2 and TiO2 obtained in step S4, heat to 50-70°C, stir and react for 2-3h, then add 2-3 parts by weight of a film-forming aid, 1-2 parts by weight of a leveling agent, and 2-3 parts by weight of a defoaming agent, stir and mix for 20-30min, let stand for 2-3h, and filter through a 100-mesh sieve to obtain a waterborne thermal transfer special release coating; The film-forming aid comprises a mixture of propanol and ethylene glycol monobutyl ether in a mass ratio of 4-6:1-2; The silane coupling agent in step S5 is a mixture of KH550 and KH792, with a mass ratio of 2-3:5-7.
10. The method for preparing the water-based thermal transfer special release printing material according to claim 1, characterized in that: The water-based ink is water-based acrylic ink; the amount of wet glue applied is 5-10g / m 2 The coating speed is 50-70m / min; the curing conditions are 100-150W UV lamp irradiation curing for 10-15min, the temperature is 120-150℃; the coating amount of the transfer glue is 5-7g / m 2 , the drying tunnel temperature is 85-105℃, and the line speed is 70-155m / min.
11. A water-based thermal transfer special release printing material prepared by the preparation method according to any one of claims 1 to 10.
Citation Information
Patent Citations
Plastic shell material for instrument panel of two-wheeled electric vehicle
CN115160726A
Production of inorganic glass or ceramic coated substrates, useful as optical or electronic components, comprises application of nanoscale particles and water soluble organic plasticizers
DE10018697A1